PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION BERBANTUAN CANVA TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD - Sari, Terigas; Sulistri, Emi; Anitra, Rien (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to determine whether there is an effect of the cooperative learning model of the Group Investigation type assisted by Canva on fifth-grade students’ learning outcomes in IPAS at SDN 29 Singkawang. The research used a quasi-experimental design, specifically a one-group pretest-posttest design. The population of this study consisted of fifth-grade students at SDN 29 Singkawang, with total sampling used as the sampling technique. The results showed that: (1) there is a significant effect of the Group Investigation cooperative learning model assisted by Canva on students' IPAS learning outcomes. This is evidenced by the Wilcoxon test result where the z_calculated value was 21.53, while the z_table value was 1.96, indicating that z_calculated ? z_table. The effect size test yielded a value of 1.28, which indicates a high effect of the Canva-assisted Group Investigation model on student learning outcomes; (2) there was an improvement in students’ learning outcomes after using the Canva-assisted Group Investigation model. This is supported by the N-Gain test result of 0.45, which falls into the medium category with a percentage gain of 45%. Based on these findings, the Canva-assisted Group Investigation learning model can be used as an alternative model and media for teaching.